Reflexology massage [videorecording (DVD)] - Mills, Bob; Gillanders, Ann; Blake, Clark (Naturaljourneys, 2003)
Instruction in reflexology, the practice of manipulating nerves in the feet, hands, or ears (this program focuses on reflexology of the feet) to alleviate various health problems elsewhere in the body, including: PMS; stress and fatigue; headache; arthritis; insomnia; depression; digestive problems; common children's ailments; heart disease; menopausal problems; asthma.